Subtleties of catanionic surfactant reverse micelle assemblies revealed by a fluorescent molecular probe - Villa Perez, Cristian (2017)
In this work, the absorption and emission behavior of the cationic hemicyanine trans-4-[4(dimethylamino)styryl]-N-methylpyridinium iodide (HC) in reverse micelles (RMs) formed by the catanionic surfactants benzyl-n-hexadecyldimethylammonium-1,4-bis-2-ethylhexylsulfosuccinate (AOT-BHD) and cetyltrimethylammonium-1,4-bis-2-ethylhexylsulfosuccinate (AOT-CTA) have been investigated. Our results show that the spectroscopic behavior of HC changes when the dye is dissolved in AOT-BHD or in AOT-CTA RMs. While HC undergoes an intramolecular charge-transfer process upon excitation in AOT-CTA RMs, in AOT-BHD RMs this process is inhibited due to a specific interaction between HC and the polar head group of the BHD+ cation. This implies that the chemical structure of CTA+ and BHD+ cations has a large impact on the excited stated from which HC emission occurs. Additionally, the structural difference between the two cations impacts on the water–RM interface interaction, which provides a way of controlling the solvation process in these RMs. Furthermore, differences in the interfacial fluidity between the two catanionic RMs is observed, a result that is particularly interesting with regard to these systems being used as nanoreactors.